2012
DOI: 10.3389/fphys.2012.00181
|View full text |Cite
|
Sign up to set email alerts
|

The use of Diagnostic Imaging for Identifying Abnormal Gas Accumulations in Cetaceans and Pinnipeds

Abstract: Recent dogma suggested that marine mammals are not at risk of decompression sickness due to a number of evolutionary adaptations. Several proposed adaptations exist. Lung compression and alveolar collapse that terminate gas-exchange before a depth is reached where supersaturation is significant and bradycardia with peripheral vasoconstriction affecting the distribution, and dynamics of blood and tissue nitrogen levels. Published accounts of gas and fat emboli and dysbaric osteonecrosis in marine mammals and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…DON does not feature as an immediate complication in persons presenting with symptoms of generalized decompression sickness 9 . The specific lesions of bone necrosis, per se, are not detected by even sophisticated MRI evaluation at the early stages of the dysbaric injury 8,11,16,22 . However, gas bubbles in the marrow can be picked up using MR techniques 8,22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DON does not feature as an immediate complication in persons presenting with symptoms of generalized decompression sickness 9 . The specific lesions of bone necrosis, per se, are not detected by even sophisticated MRI evaluation at the early stages of the dysbaric injury 8,11,16,22 . However, gas bubbles in the marrow can be picked up using MR techniques 8,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The specific lesions of bone necrosis, per se, are not detected by even sophisticated MRI evaluation at the early stages of the dysbaric injury 8,11,16,22 . However, gas bubbles in the marrow can be picked up using MR techniques 8,22 . Other causes of aseptic bone necrosis being ruled out, lesions specific to DON can take months to develop 1,17,21,[23][24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This occurs due to the inherent time gain compensation built into most systems to allow increasing amplitude of signals returning from deeper structures to compensate for attenuation (Dennison et al 2012).…”
Section: Artifactsmentioning
confidence: 99%
“…A more recent study has shown that the gas bubble composition in stranded whales is similar to that from land mammals suffering DCS in experimental dive models (Bernaldo De Quirós et al, 2012). Imaging work in both live and stranded marine mammals indicates that they live with elevated inert gas tensions that cause bubbles to form under certain circumstances (Dennison et al, 2012). This raises some interesting questions: are marine mammals ever at risk of DCS, and if so, could N 2 accumulation limit dive performance (Hooker et al, 2009;Kvadsheim et al, 2012;Sivle et al, 2012)?…”
mentioning
confidence: 99%